2010
DOI: 10.1016/j.yhbeh.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Gestational exposure to bisphenol A and cross-fostering affect behaviors in juvenile mice

Abstract: Bisphenol-A (BPA) is a component of polycarbonate resins, and, lately, concern has been raised about its potential negative effects on human health. BPA is an estrogen analog and, in addition, it can act as a DNA hypomethylator. We examined effects of gestational exposure to BPA on several behaviors in C57BL/6J mice. Because BPA affects maternal care, which, may have long-lasting effects on offspring behavior, we tested mice raised by either biological or fostered dams. Both diet and dam affected behavior in j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
103
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 53 publications
10
103
0
Order By: Relevance
“…In our experiments, maternal diet exposure to BPA was 50 mg BPA/kg feed weight, which is consistent with prior studies that have demonstrated that such a dose can induce epigenetic (21) and behavioral changes (22) in laboratory rodents. It was designed to be well below the diet-administered maximum nontoxic dose for rodents (200 mg/kg body weight per day), within the presumptive no observed effect level for mice (23), and likely to provide circulating serum concentrations close to those observed for humans (24).…”
Section: Discussionsupporting
confidence: 90%
“…In our experiments, maternal diet exposure to BPA was 50 mg BPA/kg feed weight, which is consistent with prior studies that have demonstrated that such a dose can induce epigenetic (21) and behavioral changes (22) in laboratory rodents. It was designed to be well below the diet-administered maximum nontoxic dose for rodents (200 mg/kg body weight per day), within the presumptive no observed effect level for mice (23), and likely to provide circulating serum concentrations close to those observed for humans (24).…”
Section: Discussionsupporting
confidence: 90%
“…It is important to note that effects on the mother may affect her offsprings' behavioral and neural development (97). One major challenge is to distinguish the direct effects of EDC exposures on the pups from indirect effects observed in pups due to altered maternal behaviors (28,29,98). In a small number of studies, cross-fostering has been used to isolate the "direct" effects of EDC exposures on the mother's behavior from "indirect" effects on offspring (29, 98, 99).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-fostering experiments will be necessary to delineate whether the effects of exposures on the F1 generation are direct or indirect. However, care must be taken in study design as maternal behavior can be affected in both a positive and negative direction by crossfostered pups (29,(100)(101)(102).…”
Section: Discussionmentioning
confidence: 99%
“…This observation is important, as BPA is a chemical ubiquitous in the environment and may disrupt a range of processes controlled through steroid receptors, particularly ESR1 (24)(25)(26). In view of the importance of the effects of diet on the expression of the A vy allele and considerable media and scientific attention paid to the papers describing the phenomenon (22,23), we have examined the coat color pattern distribution of A vy /a offspring born to a/a dams exposed to three doses of BPA, ranging from relatively high (50 mg/kg fw) to low (50 μg/kg fw), but all within the "no observable adverse effect level" (27). We have also tested whether the upper 50-mg dose of BPA in combination with G, G alone, and ethinyl estradiol (EE), which provides a positive estrogen control, had any effects on coat color relative to controls where the dam had been fed a phytoestrogen-free refined diet.…”
mentioning
confidence: 99%